Composition and invertibility for a class of generalized functions in the Colombeau's theory - Villarreal, F. (Gordon Breach Sci Publ Ltd, 1998)
In this work we define the composite function for a special class of generalized mappings and we study the invertibility for a certain class of generalized functions with real values.
Keywords: generalized functions; composite function; multiplicative inverse